REWRITING THE FALL: LYRA BELACQUA’S RESISTANCE TO ADULT IDEOLOGY IN HIS DARK MATERIALS - Moore, Daniel T. (My University, 2014)
This thesis examines resistance to adult ideology by child/adolescent characters in Philip Pullmans’ His Dark Materials. Drawing on terminology provided by Maria Nikolajeva (aetonormativity) and Roberta Trites (power within repression) this paper describes the development of Lyra Belacqua, the protagonist of The Golden Compass. It identifies in Pullman’s text a particular emphasis on allowing children to develop into adolescents before subjecting them to religious or secular ideologies. This thesis works with the terms Entwicklungsroman and Bildungsroman in order to illuminate and complicate the subject-positions: adolescent, child and adult. This thesis demonstrates the particular attention to qualities of adolescence and childhood in Pullman’s works, and the effect that reconstructing adolescence as an end-point for child characters has on child protagonists, by contrast to adulthood as a destination.
Keywords: Philip; Milton; Pullman; Blake; Resistance; Aetonormativity; Young Adult; Adolescent